Instabilities in a Spherical Liquid Drop - Prud'homme, Roger (Frontiers in Space Technologies, 2022)
We examine cases of stationary vortices that can appear inside spherical liquid drops in microgravity conditions. The first case is that of an uncompressible external flow of uniform speed at infinity, leading the liquid in the drop by friction to form a Hill vortex. In the second case, the external fluid does not interact by friction with the liquid, but the drop is subjected to an axial temperature gradient causing a variation in surface tension. This time it is the induced movement which carries the internal liquid. Note that the two situations can lead to the same Hill vortex. Combined effects are envisioned. We are also interested in the time factor in these phenomena.